Brexit identities and British public opinion on China. (1st November 2019) - Chow, Wilfred M.; Han, Enze; Li, Xiaojun
Abstract: Many studies have explored the importance of public opinion in British foreign policy decision-making, especially when it comes to the UK's relations with the United States and the European Union. Despite its importance, there is a dearth of research on public opinion about British foreign policy towards other major players in the international system, such as emerging powers like China. We have addressed this knowledge gap by conducting a public opinion survey in the UK after the Brexit referendum. Our research findings indicate that the British public at large finds China's rise disconcerting, but is also pragmatic in its understanding of how the ensuing bilateral relations should be managed. More importantly, our results show that views on China are clearly split between the two opposing Brexit identities. Those who subscribe strongly to the Leave identity, measured by their aversion to the EU and antipathy towards immigration, are also more likely to hold negative perceptions of Chinese global leadership and be more suspicious of China as a military threat. In contrast, those who espouse a Remain identity—that is, believe that Britain would be better served within the EU and with more immigrants—are more likely to prefer closer engagement with China and to have a more positive outlook overall on China's place within the global community.